COMPARISON OF BOOK SHOPPING PATTERNS BEFORE AND DURING THE COVID-19 PANDEMIC USING THE FP-GROWTH ALGORITHM AT ZANAFA BOOKSTORES - Dessi Cahyanti; Inggih Permana (Informatika, Universitas Jenderal Soedirman, 2022)
The high number of active cases of the Corona virus (Covid-19) has a major impact on the trade sector, namely a decrease in sales turnover, causing a decrease in income by business actors and a decrease in people's purchasing power. This study aims to compare shopping patterns before and during the pandemic in Zanafa bookstores. The method used in the study is a qualitative approach related to the assessment of attitudes, opinions and behavior. In this study the attribute used is the name of the item / product, these attributes are categorized based on the shelves that there are 40 categories of bookshelves. Testing dataset using FP-Growth algorithm in tools with support value of 3% and confidence value of 10% and the pattern used is a pattern that has lift Ratio >1. Based on the results of the analysis, it was found that the rules before the pandemic pandemic many items were purchased simultaneously, that is, if the purchase of science would buy school books with the highest lift ratio of 2.9537, while during the pandemic many items were purchased simultaneously, that is, if the purchase of politics, it would buy the Qur'an with the highest lift ratio from the test results of 2.6165. This can be used by TBZ to get recommendations as promotional materials to increase profits and as a sales strategy on TBZ.